Bifacial weakness with paresthesias: Serial nerve conduction studies indicate diffuse demyelinating neuropathy. Issue 5 (15th March 2016) - Morgan, Catherine; Fuller, Geraint; Wakerley, Benjamin R.
ABSTRACT: Introduction: Bifacial weakness with paresthesias is a rare subtype of Guillain–Barré syndrome (GBS), characterized by facial diplegia in the absence of any other cranial neuropathies, limb weakness, or ataxia. Frequently, patients also complain of distal limb paresthesias before or at the time they develop facial weakness. Methods: We describe a man who developed post‐infective isolated symmetric facial diplegia associated with distal paresthesias. Nerve conduction studies were conducted at 4 time‐points over 6 months. Results: A monophasic disease course and presence of cerebrospinal fluid albuminocytological dissociation supported a diagnosis of bifacial weakness with paresthesias. Serial nerve conduction studies demonstrated an evolving demyelinating neuropathy with evidence of distal and proximal demyelination without conduction block, which partially resolved over time. Despite complete resolution of facial weakness within weeks, distal paresthesias persisted beyond 6 months. Conclusions: This study suggests that neuropathy in patients with bifacial weakness and paresthesias is demyelinating and diffuse. Muscle Nerve 53 : 818–822, 2016